2018
DOI: 10.1021/acsomega.7b02092
|View full text |Cite
|
Sign up to set email alerts
|

6-(Ar)Alkylamino-Substituted Uracil Derivatives: Lipid Mimetics with Potent Activity at the Orphan G Protein-Coupled Receptor 84 (GPR84)

Abstract: GPR84, a Gi protein-coupled receptor that is activated by medium-chain (hydroxy)fatty acids, appears to play an important role in inflammation, immunity, and cancer. Recently, 6-octylaminouracil (4) has been reported to act as an agonist at GPR84. Here, we describe the synthesis of 69 derivatives and analogs of 4, 66 of which represent new compounds. They were evaluated in (a) cyclic adenosine monophosphate accumulation and (b) β-arrestin assays in human GPR84-expressing cells. Potent nonbiased as well as G pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 36 publications
0
63
0
Order By: Relevance
“…cAMP assays were performed as previously described [ 24 ]. CHO cells overexpressing the human GPR84 were stimulated with forskolin (10 μM) in the absence (control) or presence of test compound for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cAMP assays were performed as previously described [ 24 ]. CHO cells overexpressing the human GPR84 were stimulated with forskolin (10 μM) in the absence (control) or presence of test compound for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…β-arrestin assays were performed as previously described [ 24 ]. Briefly, CHO cells expressing the human GPR84 with a β-galactosidase fragment and β-arrestin containing the complementary fragment of the enzyme were incubated with a series of compound dilutions (in DMSO, final DMSO concentration: 1%) for 90 min before adding the detection reagent (DiscoverX ® , Fremont, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an exciting avenue to exploit for potential therapeutics (Kenakin, 2018), and the chemokine receptors are examples of immune-expressed GPCRs with multiple endogenous biased ligands (Rajagopal et al, 2013). Synthetic biased agonists at GPR84 have been identified (Pillaiyar et al, 2017(Pillaiyar et al, , 2018Moghaddam et al, 2018), and recent work by Lucy et al (2019) has shown that G-protein-biased DL-175 has a diminished chemoattractant effect on human myeloid cells, while maintaining levels of phagocytosis enhancement.…”
Section: Multiple Physiological Ligandsmentioning
confidence: 99%
“…MCFAs, with a chain length of 9-14 carbons, bind GPR84 receptor [58]. It is predominantly expressed in immune system-related tissues and cells, such as bone marrow, spleen, lung, lymph nodes and brain microglia, and adipose tissue [59]. It is suggested that GPR84 is a proinflammatory receptor [60] and it could play a role in linking fatty acid metabolism and immune responses [61].…”
Section: G-protein-coupled Receptor 84 (Gpr84)mentioning
confidence: 99%